Influence of Emotional Intelligence on the Military Training Performance among Military Trainees in Nigeria - Legbeti, Grace Ohunene; Agwu, Joshua Chukwuebuka (NIU Journal of Social Sciences, 2026)
The purpose of this study was to examine the influence of emotional intelligence on the military training performance of Nigerian military trainees. Using a cross-sectional survey design, a total of 142 participants were selected by convenience sampling technique from two military training institutions. Participants consisting of 134 males (94.4%) and 8 females (5.6 %) within an age range of 18-25 years across training years, arm of service and battalions made up the sample population. The Brief Emotional Intelligence Scale (BEIS-10) and the Self-rated Training performance Scale were used for data collection. The result of hypothesis one showed an insignificant relationship between all emotional intelligence dimensions and military training performance among military trainees while the second hypothesis was confirmed as it showed that demographic variables jointly predicted military training performance of trainees ( R = .259; F = 1.953, P< .05) but only gender independently predicted military training performance of trainees at a significant level ( β = .241; t= 2.791, P < .05). The findings were discussed and recommendations were made. Keywords: Emotional intelligence, Military Performance, Military Trainees, Military Training Performance, Nigeria